Environmental design criteria to stimulate creative thinking a case study of polytechnic campus in Merlimau Melaka - Shaari, Shamsul Johari; Mohd Ali, Noor Azizi; Abu Bakar, Shamsul (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
Outdoor learning environment (OLE) is one of the important factors that can affect students’ well- being. Besides the formal classroom-based learning, research has proven that the layout of OLE and its physical setting can influence students’ attitude, mood, behaviour and their academic achievement (Samsudin, 2007). The same notion stated by Johnson (2000) that OLE can be the place or “facility” that can support the learning process. OLE is also known as refuge spaces for the students to escape from the demanding university’s life, thus it is not surprising that most of the current campus landscape planning are focusing more on achieving highest level of students’ comfort and safety. Unfortunately, even with all these studies to improve student’s well being, there is lack of understanding on how OLE can be a place that helps to stimulate students’ creative thinking. This is a major concern due to the fact that higher learning institution should also provide the students with environments that can nurture their creativity. According to Samsudin (2007), high-quality campus environment can also generate ‘self- questioning’ or new discovery and able to encourage critical discussion among the students. Therefore, this study attempt to identify significant environmental design criteria associated with higher learning institution OLE that can be used to promote and enhance students’ creative thinking particularly from the students’ perspectives. Using survey questionnaires, a total of 90 students’ respondents from Civil Engineering, Architecture, and Land Survey programs from Merlimau Polytechnic in Melaka were involved in the study. Result of this study shows that environmental condition, activities provided and landscape elements are the important factors that can shape students’ behavior and their attitudes. It was also found that OLE with fun activities and colourful landscape can also enhance the process of developing ideas and improving students’ excellence.